2009
DOI: 10.1007/s11882-009-0082-6
|View full text |Cite
|
Sign up to set email alerts
|

Does Exposure to Indoor Allergens Contribute to the Development of Asthma and Allergy?

Abstract: Common indoor allergens include house dust mite, cockroach, animal dander, and certain molds. In genetically susceptible children, exposure to these indoor allergens during the critical postnatal period may lead to sensitization in early childhood. Consistent evidence indicates that children sensitized to common indoor allergens are at several-fold higher risk of asthma and allergy. Due to conflicting evidence from prospective studies, some doubt remains regarding a direct and dose-response relationship betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
1
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(58 citation statements)
references
References 61 publications
0
50
1
7
Order By: Relevance
“…It is generally accepted that short periods of high exposure are possibly more important than the equivalent "dose" accumulation at a lower exposure over a long time 31) . In addition to the amount of allergen, the exposuresensitization relationship may be modified by some other factors, such as parental heredity, viral infections, and concomitant pollutant exposure 32) . It also has been suggested that the effect of animal allergen is a result of increased levels of endotoxin, which may have dual effects on asthma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that short periods of high exposure are possibly more important than the equivalent "dose" accumulation at a lower exposure over a long time 31) . In addition to the amount of allergen, the exposuresensitization relationship may be modified by some other factors, such as parental heredity, viral infections, and concomitant pollutant exposure 32) . It also has been suggested that the effect of animal allergen is a result of increased levels of endotoxin, which may have dual effects on asthma pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…43 This study provided limited but useful information on the contamination of cereal and cereal-based foods with B. tropicalis allergens that carries two risks for a population: first, the sensitization of the general population via long-term ingestion of allergen-contaminated food and second, aggravated manifestations in patients with preexisting allergic disease. 44 Blo t 5 allergen should become a routine allergen considered in the clinical diagnosis of patients who complain of an apparent food allergy. Our result is limited by the small sample size, targeting Blo t 5 allergen only; a lack of a microscopic parasitological examination of the samples; and the study of risk factors that affect food contamination with mites in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Allergic diseases are common chronic diseases, and their prevalence is increasing in Croatia and in many European countries (6,(15)(16)(17)(18). The geneenvironment interactions have a signifi cant role in the sensitisation and exacerbation of childhood asthma, particularly in urban households (2,3,11,19).…”
Section: Indoor Allergensmentioning
confidence: 99%
“…Exposure to mite allergens Der p 1, and Der f 1 of 2 μg g -1 and 10 μg g -1 of dust has been regarded as a risk factor for sensitisation and asthma, respectively. However, in sensitised individuals with mild asthma, repeated exposure to low allergen level may lead to chronic asthma (18). …”
Section: Threshold Values For Indoor Allergensmentioning
confidence: 99%